Development of Sensor for the Real-time Monitoring of Brake Pad Wear and Brake Disc Temperature in High Temperature - Yoo, Jung Joo; Byun, Kyung Seok (International journal of automotive technology, 2023)
As the technology for high-performance automobiles is developing rapidly together with the significant growth of the automobile industry in modern society, customer demand for automobile safety is increasing accordingly, and thus the development of safety products is gaining momentum. The brake system is indispensable for safe driving of the automobile, and malfunction or disorder of the brake system can lead to serious accident, resulting in injury or death. Meanwhile, if the brake system can be monitored on a real-time basis, such monitoring system can notify drivers of dangerous circumstance, like excessive wear of brake pad, or overheating of brake disc. However, in the case of high-performance/oversize automobiles, frequent or sudden braking during summer causes disc temperature to rise above 600 °C, which affects the useful life of the sensor. In contrast, there has not yet been a breakthrough for the sensor that can be used in a condition that exceeds 600 °C. Based on the heat transfer theory, we have developed the sensor in this study that normally works under the temperature exceeding 600 °C and verified that the sensor works normally under the temperature of ≥825 °C.